Analisis Penerapan Metode Activity Based Costing dalam Menentukan Harga Pokok Produksi Batik Gajah Oling pada UD Batik Tatsaka Kabupaten Banyuwangi - Tiara, Tiara; Mardiana, Siska Leli; Ani, Hety Mustika (Universitas Ivet, 2024)
This research aims to analyze the use of the activity based costing method in determining the production costs of Gajah Oling Batik at UD Batik Tatsaka, Banyuwangi Regency. This research is quantitative descriptive. The data collection methods used are interview and documentation methods. The data analysis used in this research is quantitative descriptive data analysis. The research results show that there is a difference in costs resulting from calculating production costs using traditional methods and activity based costing methods, namely IDR 5,469 for written batik and IDR 444 for stamped batik. This difference in calculations occurs due to differences in several factory overhead costs. This calculation experienced undercosting because the production costs calculated by the company were too low compared to the actual calculation using the activity based costing method. Comparison of the results of calculating the cost of production using these two methods produces greater calculations for all products produced, both written batik and stamped batik at UD Batik Tatsaka. The calculations charged by UD Batik Tatsaka can be said to be subject to cost distortion. The resulting cost distortion is undercosting. This calculation experienced undercosting because the cost of goods produced was too low compared to the results of calculations using the activity based costing method. Calculation of the cost of production using the activity based costing method can show the actual costs incurred at UD Batik Tatsaka. The results obtained from calculating actual production costs are more precise and accurate compared to the calculation results charged by UD Batik Tatsaka. So it can be said that calculating actual costs using the activity based costing method is more suitable because this method can allocate all cost calculations used in production activities more precisely by looking at the consumption of each product.